Chondroprotective and anti-inflammatory effects of S-methylisothiourea, an inducible nitric oxide synthase inhibitor in cartilage and synovial explants model of osteoarthritis. (20th February 2014) - Balaganur, Venkanna; Pathak, Nitya Nand; Lingaraju, Madhu Cholenahalli; More, Amar Sunil; Latief, Najeeb; Kumari, Rashmi Rekha; Kumar, Dinesh; Tandan, Surendra K
Abstract: Objectives: To study the chondroprotective and anti-inflammatory potential of inducible nitric oxide synthase (iNOS) inhibitor S-methylisothiourea (SMT) in in-vitro model. Methods: Rabbit cartilage explants were stimulated with recombinant human interleukin 1β (rhIL-1β), and the chondroprotective and anti-inflammatory effects of SMT were investigated. Rat synovial explants were stimulated with LPS, and the anti-inflammatory effect of SMT on synovium was studied. To examine the role of SMT in synovial inflammation mediated cartilage damage, LPS stimulated synovial explants were cultured with dead cartilage with or without SMT for 72 h. The culture medium was analysed for sulfated glycosaminoglycans (GAGs) and hydroxyproline as measure of proteoglycans and collagen degradation, respectively. Key findings: SMT significantly reduced GAGs, hydroxyproline, matrix metalloproteinase (MMP)-13, tumour necrosis factor alpha (TNF-α), prostaglindin E2 (PGE2 ) and nitrite release in stimulated rabbit cartilage media indicating chondroprotective and anti-inflammatory effects of SMT in osteoarthritis (OA). Stimulated synovial explants caused release of nitrite, PGE2, IL-1β and TNF-α in the medium which were significantly reduced by SMT indicating its anti-inflammatory action. SMT significantly reduced GAGs and hydroxyproline in medium and shown protective effect against synovium-mediated cartilage damage. Conclusions: SMT inhibited cartilage degradation, synovial inflammation and synovium-mediated cartilage damage, suggesting that SMT may be an agent for pharmacological intervention in OA.